In Great Haste to See a Play: A Woman Playgoer in Jacobean Worcester - Pangallo, Matteo (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2025)
This note transcribes a letter written by Mary Ingram of Worcester sometime between 1607 and 1614, in which she describes going to see a play. The note provides some context about Mary, and her sister to whom she sent the letter, and what performance she might have gone to see, and what her letter reveals about early modern women as playgoers in the provinces.